Evaluation of Antimicrobial Potential using Disc Diffusion Assay of Seagrape Macroalgae Extract (Caulerpa sp.) in the waters of Pasaran Island, Lampung as an Anti-Inflammatory Agent - Nurjanah, Annisa; Kurniawan, Eri Surya; Giani, Giani; Prasetyo, Deni; Pramesti, Gustiviana Shandy; Rahmando, Revo Aulia; Syafitri, An; Umam, Fais Safiqul; Putri, Wanda Andella; Amiin, Muhammad Kholiqul (Biology, Medicine, & Natural Product Chemistry, 2025)
Sea grape (Caulerpa sp.) is a green seaweed species with bioactive content consisting of flavonoids, terpenoids, alkaloids, and phenols. This study evaluates the antimicrobial potential of Sea*Grape macroalgae extract (Caulerpa sp.) obtained from Pasaran Island, Lampung. The diffusion assay method assessed the antimicrobial activity of Caulerpa sp. extract against Staphylococcus aureus. Caulerpa sp. samples were extracted using the maceration extraction method and evaporated using two methods: water bath and rotary evaporator. The results showed that Caulerpa sp. extract had antimicrobial activity at a concentration of 10,000 ppm, which was resistant to Staphylococcus aureus. These findings suggest that Caulerpa sp. from the waters of Pasaran Island has the potential to be a source of natural antimicrobial and anti-inflammatory components if the concentration of the extract is more significant, which can be further developed for applications in the health and pharmaceutical fields.